Wireless Networks for Dummies - Lewis, Barry (Wiley Publishing, 2011)
Wireless Networks For Dummies was coauthored by Barry D. Lewis, CISSP, and Peter T. Davis, who also coauthored Computer Security For Dummies. Barry Lewis is president of an information security consulting firm and an internationally known leader of security seminars. Peter Davis is founder of a firm specializing in the security, audit, and control of information. Together, they cut through the cables, clutter, and confusion and help you: